Metabolism of inhaled methylethylketone in rats. (2nd January 2018) - Cosnier, Frédéric; Grossmann, Stéphane; Nunge, Hervé; Brochard, Céline; Muller, Samuel; Lambert-Xolin, Anne-Marie; Sebillaud, Sylvie; Rieger, Benoît; Thomas, Aurélie; Décret, Marie-Josèphe; Burgart, Manuella; Gaté, Laurent; et al.
Abstract: Methylethylketone (MEK) is widely used in industry, often in combination with other compounds. Although nontoxic, it can make other chemicals harmful. This study investigates the fate of MEK in rat blood, brain and urine as well as its hepatic metabolism following inhalation over 1 month (at 20, 200 or 1400 ppm). MEK did not significantly accumulate in the organism: blood concentrations were similar after six-hour or 1-month inhalation periods, and brain concentrations only increased slightly after 1 month's exposure. Urinary excretion, based on the major metabolites, 2, 3-butanediols (± and meso forms), accounted for less than 2.4% of the amount inhaled. 2-Butanol, 3-hydroxy-2-butanone and MEK itself were only detectable in urine in the highest concentration conditions investigated, when metabolic saturation occurred. Although MEK exposure did not alter the total cytochrome P450 concentration, it induced activation of both CYP1A2 and CYP2E1 enzymes. In addition, the liver glutathione concentration (reduced and oxidized forms) decreased, as did glutathione S-transferase (GST) activity (at exposure levels over 200 ppm). These metabolic data could be useful for pharmacokinetic model development and/or verification and suggest the ability of MEK to influence the metabolism (and potentiate the toxicity) of other substances.